A Case of Hodgkin Lymphoma Presenting as Nephrotic Syndrome - Dakhane, Yogesh Rambhau; Singh, Rajesh Kumar; Thapar, Rajeev Kumar (Journal of Nepal Paediatric Society, 2016)
Nephrotic changes as part of the paraneoplastic syndrome are rare in lymphoid malignancies. One percent of cases of Hodgkin's Lymphoma cases may present with nephritic syndrome. We are reporting a case which initially presented as nephritic syndrome and later was diagnosed to have of Hodgkin's Lymphoma and managed accordingly. J Nepal Paediatr Soc 2016;36(1):72-74.